African primary care research: Reviewing the literature - Andrew Ross; Bob Mash (AOSIS, 2014)
This is the second article in the series on African primary care research. The article focuses on how to search for relevant evidence in the published literature that can be used in the development of a research proposal. The article addresses the style of writing required and the nature of the arguments for the social and scientific value of the proposed study, as well as the use of literature in conceptual frameworks and in the methods. Finally, the article looks athow to keep track of the literature used and to reference it appropriately.